Analysis of the Debt-paying Ability of Listed Companies: A Case Study Using BYD Company as a Sample - Zhuo Tonghui (SHS Web of Conferences)
This paper gives a complete knowledge of BYD’s financial performance through a thorough examination of its financial statements and related indicators. First, the history and development of BYD company are reviewed, and its main business scope and operating conditions are summarized to provide comprehensive background information for the subsequent solvency analysis. Second, this study uses the theoretical framework of solvency to define the important elements that influence solvency, as well as to introduce the generally used solvency evaluation indicators. Finally, in light of the research findings, a number of improvement solutions are offered, including asset structure adjustments and capital structure optimization, to improve BYD’s solvency. The study’s findings seek to provide investors, management, and researchers with a thorough grasp of BYD’s financial status, as well as practical ideas for future development.